2015
DOI: 10.1007/s00484-014-0949-7
|View full text |Cite
|
Sign up to set email alerts
|

Wet-bulb globe temperature index estimation using meteorological data from São Paulo State, Brazil

Abstract: It is well known that excessive heat exposure causes heat disorders and can lead to death in some situations. Evaluation of heat stress on workers performing indoor and outdoor activities is, nowadays, conducted worldwide by wet-bulb globe temperature (WBGT) index, which calculation parameters are dry-bulb, natural wet-bulb, and globe temperatures, which must be measured at the same time and in location where the worker is conducting his/her activities. However, for some activities performed in large outdoor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 31 publications
1
21
0
12
Order By: Relevance
“…Many indices have been used to investigate thermal comfort in outdoor areas (Matzarakis and Mayer, 1997;Gómez et al, 2004;Emmanuel, 2005;Andrade and Alcoforado, 2008;Lai et al, 2014;Hirashima et al, 2016). The wet-bulb globe temperature (WBGT), which uses meteorological data in its estimates, has been widely used by many authors to assess occupational exposure to extreme heat in outdoor working sites (Dernedde and Gilbert, 1991;Bernard and Pourmoghani, 1999;Hunter and Minyard, 2000;Tonouchi et al, 2006;Liljegren et al, 2008;Gaspar and Quintela, 2009; Australian Bureau of Meteorology, 2013; Maia et al, 2015). Some authors have used numerical simulations to analyse the WBGT, or other indices, in order to help mitigate the effects of heat exposure (Bernard and Hanna, 1988;Kusaka et al, 2012;Kjellstrom et al, 2013;Kikumoto et al, 2016;Ohashia et al, 2016;Zheng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many indices have been used to investigate thermal comfort in outdoor areas (Matzarakis and Mayer, 1997;Gómez et al, 2004;Emmanuel, 2005;Andrade and Alcoforado, 2008;Lai et al, 2014;Hirashima et al, 2016). The wet-bulb globe temperature (WBGT), which uses meteorological data in its estimates, has been widely used by many authors to assess occupational exposure to extreme heat in outdoor working sites (Dernedde and Gilbert, 1991;Bernard and Pourmoghani, 1999;Hunter and Minyard, 2000;Tonouchi et al, 2006;Liljegren et al, 2008;Gaspar and Quintela, 2009; Australian Bureau of Meteorology, 2013; Maia et al, 2015). Some authors have used numerical simulations to analyse the WBGT, or other indices, in order to help mitigate the effects of heat exposure (Bernard and Hanna, 1988;Kusaka et al, 2012;Kjellstrom et al, 2013;Kikumoto et al, 2016;Ohashia et al, 2016;Zheng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Maia et al . () measured the WBGT index using meteorological data in Brazil and found that the correlation between the estimated and actual values was about 0.77. In the present study, the correlation co‐efficient between the calculated and estimated black globe temperature was 0.952, which indicates that the model is appropriate to estimate the black globe temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo, utiliza-se o método proposto recentemente por Maia et al 48 , o qual utilizou dados meteorológicos observados no Estado de São Paulo para o seu desenvolvimento. A formulação é baseada no método proposto por Hunter & Minyard 41 .…”
Section: Estimativa Do Ibutg E Método De Análiseunclassified
“…A formulação é baseada no método proposto por Hunter & Minyard 41 . Uma das principais adequações apresentadas por Maia et al 48 foi a consideração de variação da fração de radiação direta do sol (f db ) e da fração de radiação difusa (f dif ), parâmetros considerados constantes por Hunter & Minyard 41 . Segundo Maia et al 48 , essa consideração garante uma maior precisão na estimativa do IBUTG, pois contabiliza os efeitos da nebulosidade, situação que comumente ocorre em dias quentes no Estado de São Paulo.…”
Section: Estimativa Do Ibutg E Método De Análiseunclassified
See 1 more Smart Citation